2022
DOI: 10.3389/fnut.2022.891241
|View full text |Cite
|
Sign up to set email alerts
|

Four-Week Supplementation of Water-Soluble Tomato Extract Attenuates Platelet Function in Chinese Healthy Middle-Aged and Older Individuals: A Randomized, Double-Blinded, and Crossover Clinical Trial

Abstract: Background and AimsPlatelets are linked to atherosclerotic development and pathological thrombosis. Single dose of water-soluble tomato extract (WTE) which is a natural extraction can exert anti-platelet effects after 3 or 7 h in British healthy people. However, the effects of WTE supplementation on platelet function in Chinese healthy middle-aged and older individuals have not been studied, and the effects or safety of 4-week WTE supplementation also remain unclear. The present study aims to determine the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…These adhesion molecules trigger the inflammatory response, characterized by a complex interplay between platelets, leukocytes, and endothelial cells. A previous study showed that the WSTC supplementation for 4 weeks could moderately reduce platelet activation, aggregation, and granule secretion in older individuals with low shear rates (38). Together with our study, both represented a similar opinion of maintaining normal platelet aggregation which is good for healthy blood flow and vice versa.…”
Section: Discussionsupporting
confidence: 86%
“…These adhesion molecules trigger the inflammatory response, characterized by a complex interplay between platelets, leukocytes, and endothelial cells. A previous study showed that the WSTC supplementation for 4 weeks could moderately reduce platelet activation, aggregation, and granule secretion in older individuals with low shear rates (38). Together with our study, both represented a similar opinion of maintaining normal platelet aggregation which is good for healthy blood flow and vice versa.…”
Section: Discussionsupporting
confidence: 86%
“…In a double-blinded crossover study in healthy humans, it was evidenced that the consumption of tomato supplements in drink format led to a significant reduction in ex vivo platelet aggregation after 3 h [18]. In another study, it was found that a 150 mg/day watersoluble tomato extract supplement for four weeks significantly reduced ADP-induced or collagen-induced platelet aggregation in healthy middle-aged and older individuals [17]. The favorable impact of fresh tomatoes or tomato-base products on platelet aggregation is contingent upon their adequate presence of bioactive compounds (such as lycopene, flavonoids, phenolic acids, and vitamin E) [38].…”
Section: Discussionmentioning
confidence: 98%
“…To date, scientific evidence of the beneficial effects of tomato-base products on CVD and platelet aggregation has been demonstrated in in vitro [18,[35][36][37] and in vivo [17,35] studies. In a double-blinded crossover study in healthy humans, it was evidenced that the consumption of tomato supplements in drink format led to a significant reduction in ex vivo platelet aggregation after 3 h [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation